Message Reception Analysis in Intercultural Communication during "Magnetic Resonance Imaging" Training in Hospitals - Syafiq Basri Assegaff; Eunike Serfina Fajarini; Noprita Herari; Amalia Setiawati (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The utilization of Magnetic Resonance Imaging (MRI) machines is essential for accurate disease diagnoses, necessitating radiographers to undergo a ten-day training regimen. While existing studies often concentrate on interpersonal communication in healthcare, this research explores the reciprocal development of reflexive action and interpretation during MRI training in Indonesian hospitals, employing the Coordinated Management of Meaning (CMM) Theory and integrating intercultural communication obstacles. Employing participatory observation, key informant interviews, and focus group discussions, the study unveils that trainers employ both verbal and non-verbal communication, including orientation, empathy, and dynamic interactions. The results highlight reciprocal, proactive communication strategies between trainers and trainees, emphasizing mindfulness, emotional vulnerability mitigation, honest communication, and the cultivation of functional behaviors. This research contributes not only to health communication literature, particularly MRI training but also advances practical insights into intercultural communication research.